Analisis Faktor Kejadian Unmet Need KB Pada Wanita Usia Subur di Wilayah Kerja Puskesmas Wae Kanta - Hamat, Viviana; Janggu, Jayanthi Petronela; Manggul, Makrina Sedista; Adar, Olivera Agnes; Kurniati, Kornelia (Universitas Malahayati, 2024)
ABSTRACT Indonesia is still one of the countries with the largest population in the world. One of the programs carried out by the government is the Family Planning Program to control the population and improve the health welfare of mothers and children. However, the high unmet need is a problem for the government not only regarding the population explosion in 2030 but will also increase the maternal mortality rate (MMR) in Indonesia. To analyze the factors that influence the decision to unmet need for family planning among female couples of childbearing age in the Wae Kanta Community Health Center working area. This study is quantitative with a cross sectional design. Data collection uses a structured questionnaire that has been tested and declared valid. The research was conducted in the target village, namely Wae Kanta Village, 4-5 December 2023. The sampling technique was total sampling with a population of 37 fertile female couples. The analysis starts with univariate and then bivariate with the chi square test. There is a relationship between age and the incidence of unmet need for family planning with a p value of 0.006 (p < 0.05). There is a relationship between education and the incidence of unmet need for family planning with a p value of 0.000 (p < 0.05). There is a relationship between husband's support and the incidence of unmet need for family planning with a p value of 0.000 (p < 0.05). There is a relationship between knowledge and the incidence of unmet need for family planning with a p value of 0.002 (p < 0.05). Several factors have been proven to have an influence on the incidence of unmet need for family planning among WUS in Wae Kanta village, including mother's age, education, knowledge and husband's support. Employment, income and parity factors have no relationship with the incidence of unmet need for family planning. Keywords: Unmet Need for Family Planning Factors, Unmet Need for Family Planning, Women of Childbearing Age ABSTRAK Indonesia masih menjadi salah satu negara yang memiliki populasi terbanyak didunia. Salah satu program yang dilakukan pemerintah adalah Program Keluarga Berencana untuk mengedalikan populasi dan meningkatkan kesejahteraan kesehatan ibu dan anak. Namun Tingginya unmet need menjadi permasalahan bagi pemerintah bukan hanya perihal ledakan populasi penduduk di tahun 2030 tetapi juga akan meningkatkan angka kematian ibu (AKI) di Indonesia. Menganalisis faktor yang mempengaruhi keputusan unmet need KB pada Wanita pasangan usia subur di wilayah kerja Puskesmas Wae Kanta. Studi ini kuantitatif dengan desain cross sectional. Pengumpulan data menggunakan kuesioner terstruktur yang telah diuji dan dinyatakan valid. Penelitian dilakukan di desa binaan yaitu Desa Wae Kanta tanggal 4-5 Desember 2023. Teknik sampel adalah total sampling dengan jumlah populasi Wanita pasangan subur berjumlah 37 orang. Analisis dimulai dengan univariat selanjutnya bivariat dnegan uji chi square. Ada hubungan antara umur dengan kejadian unmet need KB dengan nilai p value sebesar 0,006 (p < 0,05). Ada hubungan antara pendidikan dengan kejadian unmet need KB dengan nilai p value sebesar 0,000 (p < 0,05). Ada hubungan antara dukungan suami dengan kejadian unmet need KB dengan nilai p value sebesar 0,000 (p < 0,05). Ada hubungan antara pengetahuan dengan kejadian unmet need KB dengan nilai p value sebesar 0,002 (p < 0,05). Beberpa faktor yang terbukti memiliki pengaruh terhadap kejadian unmeed need KB pada WUS di Desa Wae Kanta diantaranya umur ibu, Pendidikan, pengetahuan dan dukungan suami. Faktor pekerjaan, penghasilan dan paritas tidak memiliki hubungan dengan kejadian unmet need KB Kata Kunci: Faktor Unmet Need KB, Unmet Need KB, Wanita Usia Subur